MENGEKSPRESIKAN IDE-IDE MATEMATIS MELALUI TULISAN PADA MATERI BANGUN RUANG SISWA SMP - Nadhira Pramesti (Journal on Education, 2019)
Mathematical communication is a dialogue about the transfer of mathematical messages in writing or verbally containing mathematical material in the form of concepts, formulas, or problem-solving strategies. One aspect of the indicator in mathematical communication is expressing mathematical ideas through writing. This study aims to analyze the difficulties of students in working on mathematical communication problems in geometry. The approach in this study uses a qualitative research approach with descriptive methods. The instrument used in the form of communication skills test in the form of description, the number of questions as much as 1 item, the question is given to class IX students as many as 29 students in one of the Public Middle Schools in West Bandung Regency. The results of the study showed that students' ability to express mathematical ideas through writing on geometry material on mathematical questions containing 3 aspects, namely (1) Writing down the data is known and asked, (2) Solving problems with mathematical symbols, (3) Illustrating solutions with images, still relatively very low, only 16% of the students' answers reached the maximum score.